Implementasi Komunitas Belajar Terhadap Profesionalisme Guru Sekolah Dasar Di Lahan Basah - Hayati, Hikmah; Harsono, Arta Mulya Budi; Suriansyah, Ahmad (CV. ITTC INDONESIA, 2025)
This study examines the implementation of a learning community, encompassing the stages of forming, storming, norming, and performing, and its impact on teacher professionalism, encompassing pedagogical, personality, social, and professional competencies. The research employed a qualitative approach with a case study design and triangulated data from interviews, observations, and document studies. The results indicate that the implementation of a learning community improved teacher professionalism. Teachers were able to collaborate effectively, adapt to the ecological environment of wetlands, and demonstrate innovation in developing learning. Overall, the learning community was effective as a platform for enhancing teacher professionalism.